Exercise-induced re-programming of age-related metabolic changes in microglia is accompanied by a reduction in senescent cells. - Mela-Rivas, Virginia; Mota, Bibiana C.; Milner, Mark; McGinley, Aoife; Mills, Kingston H.G.; Kelly, Aine M.; Lynch, Marina Ann (Elsevier, 2020)
contribute to age-related cognitive impairment. Exercise improves cognitive function in aged animals, perhaps because of a modulatory effect on microglial activation. Recent evidence indicates that inflammatory microglia are glycolytic, driven by an increase in 6- phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3), an enzyme that is described as the master regulator of glycolysis. Here we investigated whether microglia from aged animals exhibited a glycolytic signature and whether exercise exerted a modulatory effect on this metabolic profile. Young (4 month-old) and aged (18 month-old) mice were trained for 10 days on a treadmill. One day before sacrifice, animals were assessed in the novel object recognition and the object displacement tests. Animals were sacrificed after the last bout of exercise, microglial cells were isolated, cultured for 5 days and assessed for metabolic profile. Performance in both behavioural tests was impaired in sedentary aged animals and exercise attenuated this age-related effect. A significant increase in glycolysis, glycolytic capacity and PFKFB3 was observed in microglia from aged animals and exercise ameliorated these effects, while it also increased the phagocytic capacity of cells. The senescent markers, -galactosidase and p16INK4A, were increased in microglia from sedentary aged mice, and expression of these markers was significantly decreased by exercise. The data demonstrate that the exerciserelated improved cognition is orchestrated by a normalization of the metabolic profile and functionality of microglia.
https://openpolicyfinder.jisc.ac.uk/id/publication/12478
Keywords: Ejercicio físico - Aspectos fisiológicos; Sistema nervioso - Inflamación; Glucólisis; Fagocitosis; Fosforilación oxidativa; Neuroglia; Exercise; Glycolysis; IL-1β; Microglia; Neuroinflammation; Oxidative metabolism; Phagocytosis